2014
DOI: 10.1007/s40336-014-0054-2
|View full text |Cite
|
Sign up to set email alerts
|

Peptide receptor radionuclide therapy using radiolabeled somatostatin analogs: focus on future developments

Abstract: Peptide receptor radionuclide therapy (PRRT) has been shown to be an effective treatment for neuroendocrine tumors (NETs) if curative surgery is not an option. A majority of NETs abundantly express somatostatin receptors. Consequently, following administration of somatostatin (SST) analogs labeled with γ-emitting radionuclides, these tumors can be imaged for diagnosis, staging or follow-up purposes. Furthermore, when β-emitting radionuclides are used, radiolabeled peptides (radiopeptides) can also be used for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
54
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 81 publications
0
54
0
1
Order By: Relevance
“…These include the improvement of pharmacokinetics and in vivo stability, the combination of radionuclides, the combination of PRRT with chemotherapy, the use of a-emitting radionuclides, and the use of novel methods to predict therapy response. Recent developments to increase the therapeutic effects of PRRT have been described in detail by Bison et al (13). Some examples of novel approaches for radionuclide therapy are shown in Figure 3.…”
Section: Novel Perspectives For Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…These include the improvement of pharmacokinetics and in vivo stability, the combination of radionuclides, the combination of PRRT with chemotherapy, the use of a-emitting radionuclides, and the use of novel methods to predict therapy response. Recent developments to increase the therapeutic effects of PRRT have been described in detail by Bison et al (13). Some examples of novel approaches for radionuclide therapy are shown in Figure 3.…”
Section: Novel Perspectives For Therapymentioning
confidence: 99%
“…However, careful design of such combination studies is needed, as chemotherapeutics can also alter receptor expression and tumor vascularization. For instance, the DNA alkylating drug temozolomide increased tumor perfusion in a preclinical study (13). Clinical studies combining PRRT using 177 Lu-DOTATATE with several chemotherapeutics have been reported.…”
Section: Combination Therapiesmentioning
confidence: 99%
“…Although results are positive, there is room for improvement of PRRT using SSTR radioligands. Recent developments to improve therapeutic outcome with SSTR radioligands include the use of a combination of 90 Y-and 177 Lu-labeled peptide analogs, PRRT using a-emitters, and the combination of PRRT with other anticancer agents (4). Another recent development is the introduction of SST analogs with receptor antagonistic properties.…”
mentioning
confidence: 99%
“…They have been used successfully in diagnosing patients with NET using nuclear imaging technologies, such as SPECT or PET, in combination with CT. They have also been used successfully for peptide receptor radionuclide therapy in patients with metastasized disease (2,3), although surgical resection of the tumor tissue, if possible, is the preferred treatment for NET (4,5).…”
mentioning
confidence: 99%